Constitutionality of Separating National and Regional Elections after Constitutional Court Decision 135/PUU-XXII/2024 - Habibul Umam Taqiuddin; Anggi Purnama Tradesa; Baiq Widiantari (Jurnal Ilmu Kepolisian, 2026)
Indonesia's experience with the five-ballot simultaneous election in 2019 exposed the administrative strain created when presidential, national legislative, and regional legislative contests are conducted within a single electoral cycle. The resulting burden on voters, election organisers, and electoral logistics became part of the constitutional debate that preceded Constitutional Court Decision Number 135/PUU-XXII/2024. This article examines two related issues: whether the Constitution permits national and regional elections to be placed on different schedules, and how such a redesign affects the tenure of provincial and regency/municipal Regional People's Representative Councils (DPRD). The research is normative and doctrinal, drawing on statutory, case, conceptual, and historical approaches. It finds that the 1945 Constitution does not prescribe one compulsory model of simultaneity; separation is therefore permissible so long as the legislature protects electoral periodicity, popular sovereignty, representative legitimacy, and legal certainty. The principal difficulty lies in the transition. Existing legislation does not yet provide a complete mechanism for reconciling the new regional election timetable with the statutory five-year tenure of DPRD members. Any additional period in office must consequently rest on express legislation, be confined to the minimum period required for transition, and remain compatible with Article 22E paragraph (1) of the 1945 Constitution. Legislative harmonisation is therefore necessary before the new schedule is implemented.